Socioeconomic drivers of encephalitis burden in the post-COVID era: a 204-country analysis from global burden of disease study 2021 - Wang, Yikang; Wang, Di; Tian, Yu; Yao, Yilong; Yu, Qi (Frontiers in Public Health, 2025)
BackgroundEncephalitis, an inflammatory central nervous system disease causing significant morbidity and mortality, disproportionately affects low- and middle-income countries (LMICs) due to healthcare disparities. Encephalitis has diverse etiologies—viral, autoimmune, bacterial, parasitic—each with distinct clinical and epidemiological features. Despite declining global age-standardized rates since 1990, inequities in diagnostics, vaccine coverage, and critical care persist, worsened by COVID-19 pandemic, which delayed diagnoses and disrupted vaccinations.MethodsUsing Global Burden of Disease (GBD) 2021 data, we analyzed age-standardized prevalence, incidence, mortality, and disability-adjusted life-years (DALYs) across 204 countries (1990–2021). We used the Bayesian Age-Period-Cohort model with integrated nested Laplace approximation to predict encephalitis’ future trends, through 2040, enhancing the study’s predictive value. Sociodemographic Index (SDI) stratification and Bayesian meta-regression models assessed trends, with significance determined via 95% uncertainty intervals and estimated annual percentage change (EAPC).ResultsIn 2021, 4.64 million individuals worldwide were affected by encephalitis (1.49 million new cases; 92,000 deaths), encompassing cases spanning acute, subacute, and chronic stages of the disease. Low-middle SDI regions bore 3–5 times higher burdens than high-SDI regions. South Asia had the highest burden (age-standardized prevalence rate [ASPR]: 140.9/100,000; incidence [ASIR]: 51.3/100,000), while Australasia reported the lowest (ASPR: 1.94/100,000). High-SDI countries showed distinct patterns, such as rising incidence in Australia. COVID-19 was associated with an 18% increase in DALYs in high-burden regions. National disparities were stark: Pakistan, India, and Nepal had the highest burdens; Canada, the lowest. The encephalitis burden was greater in children than in other age groups.ConclusionThis analysis advances prior GBD research by integrating post-COVID-19 insights and future burden forecasts, filling pre-pandemic study gaps. GBD dataset does not differentiate etiological subtypes, limiting our analysis granularity given encephalitis’ clinical and epidemiological heterogeneity. Socioeconomic inequities drive encephalitis burden, necessitating targeted interventions: scaling Japanese encephalitis vaccination in South Asia, strengthening African diagnostic hubs, and integrating climate-resilient surveillance. Post-pandemic recovery must prioritize healthcare infrastructure, telehealth, and policies addressing poverty and education. Global collaboration is critical to mitigate disparities and optimize region-specific strategies.